PENGARUH KUALITAS PRODUK, HARGA,DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CAFE KOPI LIVING - I MADE MURJANA; YUSI FAIZATHLOCTAVI; ROSYIA WARDANI; NENDY PRATAMA AGUFIANTO (GANEC SWARA, 2023)
This study aims to determine the significane of the effect of product quality, price, service quality partially and simultaneously on consumer satisfaction of living cafe coffee. This type of research is associative research. The population in this study is the Coffee Living Cafe visitors whose population is unknown. The number of samples taken is as many as 80 respondents, data collection techniques using observation and questionnaires. Data analysis using multiple linear regression analysis showed (Y= 0.670 + 0.340 X1 + 0.181 X2 + 0.740 X3 + e). Based on the results of the partial hypothesis test that product quality, price, and service quality have a significant effect on consumer satisfaction for living cafe coffee. Where is the product quality (X1) with t count (6,101) > t table (1,990). Price (X2) with t count (3.095) > t table (1.990). Service quality (X3) with t count (4,974) > t table (1,990). Simultaneously product quality, price, and service quality have a significant effect on customer satisfaction with f count (165,072) > f table (2,72) with a significance of 0,000. Product quality variable is the most dominant variable affecting consumer satisfaction with a beta value (0.340)